2014
DOI: 10.1038/srep06295
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Platinum Mass Activity on the Surface of Polymer-wrapped Carbon Nanotube-Based Fuel Cell Electrocatalysts

Abstract: Cost reduction and improved durability are the two major targets for accelerating the commercialization of polymer electrolyte membrane fuel cells (PEFCs). To achieve these goals, the development of a novel method to fabricate platinum (Pt)-based electrocatalysts with a high mass activity, deposited on durable conductive support materials, is necessary. In this study, we describe a facile approach to grow homogeneously dispersed Pt nanoparticles (Pt) with a narrow diameter distribution in a highly controllable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…For the MWNT/PyPBI/Pt (Fig. 3a), the peaks due to the N 1s at~400 eV derived from the imidazole in the PyPBI [22] and Pt 4f at around 72e75 eV were observed. Importantly, new peaks at~689 and 168 eV due to the F 1s and S 2p , respectively [43], were observed after the washing, suggesting successful coating of Nafion on the MWNT/ PyPBI/Pt to provide an ionomer-coated electrocatalyst (MWNT/ PyPBI/Pt-i), On the other hand, both the F 1s and S 2p peaks were not detected from the ox-MWNT/Pt after washing ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For the MWNT/PyPBI/Pt (Fig. 3a), the peaks due to the N 1s at~400 eV derived from the imidazole in the PyPBI [22] and Pt 4f at around 72e75 eV were observed. Importantly, new peaks at~689 and 168 eV due to the F 1s and S 2p , respectively [43], were observed after the washing, suggesting successful coating of Nafion on the MWNT/ PyPBI/Pt to provide an ionomer-coated electrocatalyst (MWNT/ PyPBI/Pt-i), On the other hand, both the F 1s and S 2p peaks were not detected from the ox-MWNT/Pt after washing ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It is clear that uniform Pt‐NPs are homogeneously dispersed on the MWNT/PyPBI as a result of the strong chelating effect of the Pt ion by PyPBI . In the absence of NaOH, the Pt‐NPs size was 3.8±0.4 nm as we previously reported . On the other hand, it was found that the Pt‐NP size decreased with increasing amounts of NaOH; specifically, the Pt‐NP diameters were 3.1±0.3, 2.4±0.2, 2.2±0.2, 2.0±0.2, and 1.7±0.1 nm for the electrocatalysts synthesized with 0.5, 1.0, 2.0, 4.0, and 6.0 m m NaOH, respectively, which correspond to pH values of 4.4, 4.7, 6.2, 7.3, and 10.6, respectively (before the addition of NaOH, the pH was 3.9).…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, use of a large amount of the electrocatalyst is needed to prepare a membrane electrode assembly (MEA) with a typical Pt loading (0.5–1.0 mg Pt cm −2 ). Thus, the catalyst layer becomes thicker compared with the commercial electrocatalyst containing a Pt loading of approximately 40 wt %, an effect that is a disadvantage in terms of mass transfer, suggesting the electrocatalyst is not suitable for real fuel cell applications …”
Section: Introductionmentioning
confidence: 95%
“…The Pt‐utilization in fuel cell electrocatalysts is believed to be improved by reducing the particle size of platinum or by exploring various Pt‐based bimetallic structures including core – shell,textured Pt‐alloys with Pt‐skins on top of base metals, etc. For example, Hafeez et al have demonstrated that a hydrogen‐fed fuel cell incorporating Pt particles with a size of 2.3 nm as both anode and cathode exhibit an eight‐fold increased mass activity compared to a fuel cell constructed with Pt particles with a size of 3.7 nm as both anode and cathode . Further, homogeneous deposition of Pt‐based nanoparticles on to a suitable conductive carbon supports like carbon black (CB), carbon nanotubes, graphene oxide were also explored as a convenient way to enhance the Pt utilization .…”
Section: Introductionmentioning
confidence: 97%